Overall Equpment Effectiveness : A Powerful Production/Mantenance Tool for Increased Profits - HANSEN, Robert C. (Industrial Press, 2001)
Overall Equpment Effectiveness : A Powerful Production/Mantenance Tool for Increased Profits